Cognitive style, cortical stimulation, and the conversion hypothesis - Kraemer, David J.; Hamilton, Roy; Messing, Samuel B.; DeSantis, Jennifer H.; Thompson-Schill, Sharon L. (Frontiers in Human Neuroscience, 2014)
What does it mean to have a “verbal cognitive style?” We adopt the view that a cognitive style represents a cognitive strategy, and we posit the conversion hypothesis – the notion that individuals with a proclivity for the verbal cognitive style tend to code nonverbal information into the verbal domain. Here we used repetitive transcranial magnetic stimulation (rTMS) to disrupt this hypothesized verbal conversion strategy. Following our previous research implicating left supramarginal gyrus (SMG) in the verbal cognitive style, we used an fMRI paradigm to localize left SMG activity for each subject, then these functional peaks became rTMS targets. Left SMG stimulation impaired performance during a task requiring conversion from pictures to verbal labels. The magnitude of this effect was predicted by individuals’ level of verbal cognitive style, supporting the hypothesized role of left SMG in the verbal labeling strategy, and more generally supporting the conversion hypothesis for cognitive styles.